Investigation of the microstructure change due to phase transition in nanosecond pulsed laser processing of diamond. (February 2018) - Cadot, G.B.J.; Thomas, K.; Best, J.P.; Taylor, A.A.; Michler, J.; Axinte, D.A.; Billingham, J.
Abstract: Experiments and theory are employed to investigate the thermal damage induced by infra-red nanosecond pulses in atmospheric air into a boron-doped diamond target. Micro-Raman spectroscopy, Transmission Electron Microscopy (TEM) analysis and surface topography measurement are used to investigate the carbon phase created during the rapid heating and cooling of diamond, as well as the amount of material ablated during the interaction with the laser. The analysis provides insight into the phenomena occurring for the rapid graphitisation of diamond during pulsed laser ablation, and also the microstructural disorder induced by the thermal and pressure fields at level of energy below and above the melting threshold. To support the understanding from the experimental investigations, a model is constructed for the graphitisation and ablation of diamond coupled with a collisional radiative model for the plasma evolution. The one-dimensional system of non-linear equations that model the physical processes provides an insight into the dynamics of the phenomena leading to the creation of disturbed graphite during pulsed laser ablation. Furthermore, the model helps to identify the main physical processes leading to the creation of disordered graphite, suggesting that plasma evolution does not follow a Boltzmann-Saha equilibrium and that radiative recombination is a main factor influencing the thermal evolution of the plasma and the diamond target. Finally, a good agreement with experimental findings is obtained, particularly in regards to the amount of material ablated, the thickness of the graphite layer and the processes leading to the melting of graphite. Graphical abstract: Image 1